Parametric modeling of uncut chip geometry for predicting crater wear in gear skiving - Ren, Zongwei; Fang, Zhenglong; Arakane, Takuhiro; Kizaki, Toru; Nishikawa, Tsukasa; Feng, Yannan; Kugo, Junshi; Nabata, Eiji; Sugita, Naohiko (Journal of materials processing technology, 2021)
In gear skiving, tool wear is one of the primary issues owing to the large thermomechanical cutting load. However, the effective rake angle and depth-of-cut can vary continuously throughout a single cut, leading to a complex uncut chip geometry that significantly hinders the understanding of the cutting characteristics and adds further difficulty to the prediction of tool wear. This study proposes a parametric modeling method for calculating the uncut chip geometry for each cutting pass. Developments in the rake angle and depth-of-cut (as subjected to an uncut chip) were comprehensively investigated with an aim to advance the understanding of the cutting characteristics during a single cut. Based on the uncut chip geometry, the crater wear was successfully predicted using the derived stress and temperature data, followed by a single-tooth skiving wear test verification. By comparing numerical and experimental results for crater wear, an error of less than 5 % was obtained in both depth and area. The proposed method provides a non-CAD/CAM-engine-software/environment-based alternative for calculating the process of an uncut chip geometry, clearly advancing the flexibility in further potential applications such as cutting parameter optimization and cutter design.